Mixed Messages: Using the Bible and Qur'ān in Swahili Tracts - Chesworth, John A., (Studies of Religion in Africa ;, 2022)
The present volume sets Swahili religious tracts available in Kenya and Tanzania in their context. The book starts with an overview of tracts in Swahili from the 19th century to the present day, an examination of Swahili as a religious language, and an introduction to Swahili versions of the Bible and Qurʾān. Chesworth then introduces the range of tracts currently available, examining eight in detail. In particular he considers how they present scripture in order to promote their own faith, Islam or Christianity, whilst denigrating the 'other'. Finally, the volume discusses the impact from modern media on these tracts.